EVALUASI KEJADIAN IKUTAN PASCA IMUNISASI (KIPI) VAKSIN COVID-19 DI RUMAH SAKIT UMUM PUSAT (RSUP) FATMAWATI - Maruf, Hanin (RSUP Fatmawati, 2023)
Administering the COVID-19 vaccination, local reactions such as swelling at the injection site, redness, headache and fever can also occur. Several researchers have found side effects in each type of COVID-19 vaccine with the first and second doses, but there has been no research on vaccines with the first and second booster doses. The aim of this research is to find out the type of COVID-19 booster vaccine at Fatmawati General Hospital and to find out the degree of PostImmunization Adverse Events (AEFI) in this type of vaccine. This research is a quantitative descriptive study with a cross sectional research design with data collection carried out prospectively using primary data and obtained directly through filling out online questionnaires by respondents. The sampling technique uses the Total Sampling method, namely all respondents who have met the inclusion criteria are taken as research samples, however, there is a minimum sample size of 100 respondents. Based on the data obtained, of the 100 respondents there were 56% recipients of the Pfizer booster vaccine and 44% recipients of the Indovac booster vaccine. From the percentage results for each booster vaccine, there were 56% of respondents who experienced AEFI, namely 23% AEFI for the Indovac booster vaccine and 33% for the Pfizer booster vaccine. In this study there were degrees of AEFI, namely mild degree (0%), moderate degree (14.3%) and severe degree (85.7%). The majority of booster vaccine recipients at Fatmawati General Hospital are women.